Beauty Is in the Eye of the Colonizer: South Asian-Canadian Women’s Narratives of Shadeism - Kumbhare, Shaila (Journal of Critical Race Inquiry)

(untitled) (Queen's University, 2024)
The present study investigates the experiences of second generation South Asian-Canadian women with shadeism. Two narrative interviews were conducted and analyzed thematically. Results indicate that collaborators had a desire to be fair that was shaped by their generational and intra-familial relationships as well as the media they were exposed to. This desire led to their use of make-up and skin-lightening creams to achieve fairness. Insecurity about their skin tone had a negative affect on their relationship with themselves and their social networks, including their dating life and friendships.